Tanggapan Siswa Terhadap Penerapan Program Pembiasaan Hubungannya Dengan Kemampuan Mereka Dalam Membaca Al-Qur’an - Hasbiyallah; Cecep Anwar; Ayuning Tiyas (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study was to determine: the reality of student responses to the application of the habituation program, the reality of students' ability to read the Qur'an, the reality of the relationship between students' responses to the application of the habituation program and their ability to read the Qur'an. This study uses a quantitative approach with a correlational method. Respondents are students of class VIII at SMPN 1 Cileunyi totaling 50 people. The data collection techniques used are; questionnaires, tests, observations, interviews and document studies. The data analysis techniques used are; partial analysis, normality test, regression test, correlation test and hypothesis testing. Based on the results of the study, conclusions were obtained: 1) The reality of student responses to the application of the habituation program was included in the very positive category. the average value is 4.45. This figure is in the interval 4.20 – 5.00 which means it has a very positive category. 2) The reality of students' ability to read the Qur'an is included in the sufficient category. The average value taken is 66.0. This number is in the 60-69 interval which means it has a sufficient category. 3) Reality The relationship between students' responses to the application of the habituation program (Variable X) with their ability to read the Qur'an (Variable Y) is included in a positive and significant correlation. This is based on the Spearman rank correlation test, the results show a value of 0.01% which is in the interval 0.00 0.99, which means it is categorized into a positive correlation. Based on the attached hypothesis test, it can be seen that (-0.01) < (0.279) then is rejected and 0 is accepted. The correlation used follows the linear regression equation model Y= 59.13 + 0.0077. Based on the equation, it can be seen that the (+) sign indicates an increase or increase in students' ability to read the Qur'an. The coefficient of determination reaches 1% and the remaining 99% is influenced by other factors.